Structural insights into the ubiquitin-independent midnolin-proteasome pathway - Nagesh Peddada; Xue Zhong; Yan Yin; Danielle Renee Lazaro; Jianhui Wang; Stephen Lyon; Jin Huk Choi; Xiao-chen Bai; Eva Marie Y. Moresco; Bruce Beutler (Proceedings of the National Academy of Sciences, 2025)
The protein midnolin (MIDN) augments proteasome activity in lymphocytes and dramatically facilitates the survival and proliferation of B-lymphoid malignancies. MIDN binds both to proteasomes and to substrates, but the mode of interaction with the proteasome is unknown, and the mechanism by which MIDN facilitates substrate degradation in a ubiquitin-independent manner is incompletely understood. Here, we present cryoelectron microscopy (cryo-EM) structures of the substrate-engaged, MIDN-bound human proteasome in two conformational states. MIDN induces proteasome conformations similarly to ubiquitinated substrates by using its ubiquitin-like domain to bind to the deubiquitinase RPN11 (PSMD14). By simultaneously binding to RPN1 (PSMD2) with its C-terminal α-helix, MIDN positions its substrate-carrying Catch domain above the proteasome ATPase channel through which substrates are translocated before degradation. Our findings suggest that both ubiquitin-like domain and C-terminal α-helix must bind to the proteasome for MIDN to stimulate proteasome activity.